2001
DOI: 10.1093/humrep/16.9.1950
|View full text |Cite
|
Sign up to set email alerts
|

Sperm swim-up techniques and DNA fragmentation

Abstract: We conclude that our normal swim-up technique caused no more DNA damage to spermatozoa from normal semen samples than a direct swim-up technique that involved no centrifugation step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
69
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(88 citation statements)
references
References 21 publications
11
69
0
3
Order By: Relevance
“…Several studies have investigated the efficacy of these methods with regards to the recovery of reduced percentage of sperm cells with fragmented DNA, however the results are still controversial [30,31,36,37]. While one study showed that the DGC is more effective than SUP in reducing the percentage of sperm with DNA damage [25], another one, in contrast, demonstrated that SUP recovers lower percentage of sperm with fragmented DNA as compared to DGC [37].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the efficacy of these methods with regards to the recovery of reduced percentage of sperm cells with fragmented DNA, however the results are still controversial [30,31,36,37]. While one study showed that the DGC is more effective than SUP in reducing the percentage of sperm with DNA damage [25], another one, in contrast, demonstrated that SUP recovers lower percentage of sperm with fragmented DNA as compared to DGC [37].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past years, the comparative studies on the sperm preparation methods have essentially investigated the outcomes such as the recovery rates and the conventional semen parameters [3][4][5]. And more recently, researchers have focused on the evaluation of the molecular parameters such as sperm DNA damage or apoptosis for the comparison of these different separation methods [6][7][8][9][10][11][12]. Spano et al, [7] in 1999, have been shown that the swim-up sperm separation may improve some of the sperm chromatin structure assay-related parameters.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] To date, no consensus has been achieved regarding the effect of these techniques on the DNA integrity of sperm. Several investigations have shown that sperm preparation techniques considerably reduce the level of DNA damage present in a semen sample, [4][5][6][7] while other studies have reported that these methods do not recover spermatozoa with lower incidence of DNA damage. 8 Some groups have reported that the DGC technique appreciably reduces the percentage of sperm with DNA damage, whereas the SUP method shows no significant improvement.…”
Section: Introductionmentioning
confidence: 99%
“…5,26 In the case of the SUP approach, most studies agree that this technique allows the efficient elimination of spermatozoa with high levels of DNA damage. [4][5][6] Nevertheless, none of these studies makes any distinction between the types of DNA damage present in the spermatozoa, either before or after sample processing. Therefore, the results presented in this study are novel.…”
mentioning
confidence: 99%